(3GdbGfhf GdOhdj ddHMGQ (B=s Maritime international law - (3GdaJdGhj, Sgjd MSjf,s 1941- ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2012)
(3GdbGfhf GdOhdj ddHMGQ ef GdbhGfjf GdegeI aj GdhbJ GdMGVQ(B. (3aGdHMGQ Jge GdOhd LejYG, ShGA CcGfJ SGMdI, Ce ZjQ SGMdjI(B. (3hGdHMGQ eUOQ KQGA ddHTQjI(B. (3EPG JYJeO ZGdHjI GdTYhH aj ehGQOgG GdZPGFjI Ydi eG JLhO Hg GdHMGQ ef eUGOQ egeI HgPG GdUOO(B. (3hJYO GdHMGQ CaVd hSGFd Gdfbd hCQNUgG(B. (3dgPG abO TgOJ UfGYI GdSaf GdHMQjI JWhQG cHjQG, aef GdSaf GdTQGYjI Edi Jdc GdJj JSjQ Ydi GdWGbI GdfhhjI(B. (3ceG GNJdaJ CSGdjH GdUjO aj GdhbJ GdMGVQ, hXgQJ UfGYI GdCSeGc GdMOjKI GdJj JLhH GdHMGQ(B. (3hJJHGjf GdOhd aj GdehbY GdLZQGaj, hGdbOQI Ydi GSJZdGd GdHMGQ(B. (3aHYV GdOhd JeJdc ShGMd cHjQI, bO dG JSJWjY GSJKeGQgG, hOhd eJVQQI aj ehbYgG GdLZQGaj, hCNQi dG Jedc efaPG Ydi GdHMQ, hdgG GdbOQI Ydi GdGSJKeGQ(B. (3hOhd eJbOeI JSJWjY Cf JSJMhP Ydi eUGOQ GdKQhI GdHMQjI, hCNQi ZjQ bGOQI Ydi Pdc(B. (3hGdHMGQ fbWI GdJbGA LejY GdOhd, GdeJYGQVI GdeUGdM, hGdeNJdaI GdEjOjhdhLjGJ, hGdeYGOjI(B. (3hERGA gPg GdJfGbVGJ, cGf dGHO Cf JhVY bhGYO bGfhfjI OhdjI, JSJWjY GdOhd HehLHgG GSJKeGQ GdHMGQ dUGdM GdHTQjI HTcd LjO hYGOd, hJJLfH GdefGRYGJ Hjf GdOhd(B.s
(3HHdjhLQGajI (B: (3UaMI (B301-317.s
Keywords: (3GdbGfhf GdOhdj GdHMQjs; (3Gdfbd GdHMQj (B((3bGfhf Ohdj(B)s; (3GdWQb GdeGFjI (B((3bGfhf Ohdj(B)s; (3GdedGMI (B((3bGfhf Ohdj(B)s; (3Gdfbd GdHMQj (B((3bGfhf Ohdj(B)s; (3GdehGfF (B((3bGfhf Ohdj(B)s; (3GdbGfhf GdHMQjs